Fabrication and characterization of bee pollen extract nanoparticles: Their potential in combination therapy against human A549 lung cancer cells - Nemany A.N. Hanafy; Elsayed I. Salim; Magdy E. Mahfouz; Eman A. Eltonouby; Izar H. Hamed (Food Hydrocolloids for Health, 2023)
Bee pollen extract (BPE) based polymer nanoparticles (BPENP) were fabricated in the current study by using bovine serum albumin (BSA) and the complex was then coated by folic acid conjugated protamine to be targeted for cancer cells. Spectroscopic and microscopic methods were used to characterize the resultant nanoparticles. High flavonoid and polyphenolic contents were detected by HPLC. At 336 nm, it was found that BPENP provided the highest absorption by UV. The average particle size ranged between 25 and 40 nm. The inhibitory effects and IC50 values of the acquired BPE, BPENP, Avastin, or their combination at 24 and 48 h were detected against A549 lung cancer cells. The combination therapy assay of BPENP and Avastin revealed a very significant synergism between the two drugs with a low combination index (CI). These therapies particularly the combination therapy have significantly affected the expression of the HRAS, MAPK, and apoptotic genes such as Bax, Bcl-2, and Caspase 3. It was established that obtained BPENP might be employed to support the administration of Avastin for the treatment of lung cancer.